Pengaruh Kompetensi Kepala Sekolah, Motivasi dan Kompetensi Guru terhadap Kinerja Guru serta Implikasinya pada Kompetensi Lulusan - Mas`ud Mas`ud (Kontigensi : Jurnal Ilmiah Manajemen, 2017)
The purpose of this study are to determine, access and analyze both descriptively and verificative of school / madrasah head master competency, teacher motivation, competency and performance, and also alumni competency. The method which used to analyze is path analysis. Determination of sample is use Slovin formula and to get the sampling result we use cluster proporsional stratified random sampling. Data collection is done by distribute questionnaire, interview and literature study. The descriptive results of this research show that there are weaknesses in managerial and academic supervision competency aspect of school/madrasah head master. In the teacher motivation variable, we found weakness in remuneration of the job and the quality of work environment aspect. The weaknesses of teacher competency are in the social and professional competency. We also found that the teacher performance has weakness in the aspect of evaluation or assessment of learning. In alumni competency we found the weakness in student knowledge. The verificative result found that school/madrasah head master competency, teacher motivation, and teacher competency have positive and significant impact on the teacher performance, both partially or simultaneously. Teacher performance has positive and significant impact to alumni competency.